OPTIMALISASI DIGITAL MARKETING DAN REBRANDING LOGO SEBAGAI UPAYA PENINGKATAN PEMASARAN UMKM: STUDI KASUS UMKM KERUPUK DUA UDANG DI NGAWI - Miftahul Huda; Anwar Fatoni; Ratna Alfina Nurcahyani; Nakhwa Hasanatul Aulia; Gayuh Aulia Safitri; Putri Miftakhul Jannah; Febrina Yolandha; Lusiana Suryadie Putri; Putri Fadillah Rahman; Nuri Azizah; Husna Nabila Rosyida; Ririn Maryam; Nazmah Maryam (Nusantara Hasana Journal, 2025)
The advancement of digital technology requires Micro, Small, and Medium Enterprises (MSMEs) to adapt in order to enhance competitiveness and expand market reach. This study aims to identify marketing challenges faced by the Kerupuk Dua Udang MSME and evaluate the implementation of digital marketing strategies and logo rebranding in improving product marketing. The research method used is descriptive qualitative with a case study approach, where data is collected through observations, interviews, and document analysis. The results indicate that prior to the implementation of digital marketing, the marketing efforts of this MSME were still limited to the Kendal and Ngawi sub-districts. The main challenges encountered include the lack of information on the old logo, low product visibility on digital platforms, and dependence on conventional marketing methods. The implementation of digital marketing strategies through Instagram and Shopee, along with a more professional and informative logo redesign, has proven effective in increasing product visibility and facilitating customer access to ordering. With this digital transformation, the MSME can experience growth in customer numbers and a broader market expansion. Therefore, digital marketing and rebranding strategies are recommended as solutions for other MSMEs facing similar challenges to enhance competitiveness and sustain their business in the digital era.